Improving the Teaching of Pronunciation in A Junior High School by Integrating Segmental and Suprasegmental Learning - Al Mawardi, Muhamad Rasyid; Triastuti, Anita; Nur Rohmah, Anis Ichwati (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research aimed to improve pronunciation teaching for junior high school students by integrating the learning material's segmental and suprasegmental features of pronunciation. This classroom action research was conducted in three cycles. Each cycle consists of planning, action, observation, and reflection. This study implemented six actions, i.e., 1) the use of classroom English, 2) implementing the integration of pronunciation teaching); 3) giving feedback on students’ pronunciation; 4) introducing phonetic transcription; 5) implementing engaging activities to teach pronunciation; and 6) reinforcing pronunciation. The data were collected through interviews, class observation, and pronunciation assessment using a rubric developed based on the indicators of hearing sounds, stress and intonation, and imitation. The qualitative data from the field notes and interviews were analyzed qualitatively. Meanwhile, the quantitative data from the assessment results of student pronunciation were analyzed using the paired-t test to confirm the significant difference before and after the actions. The research results show that integrating segmental and suprasegmental learning improved pronunciation teaching for Junior High School students (as reflected in the data from the interview and field notes), and their pronunciation assessment results improved student pronunciation. In all cycles, integrating segmental and suprasegmental learning in pronunciation teaching improved student pronunciation.